Development of a Virtual Reality Baking Lab Application for Bakery Students at UTHM : KitchenLab - MOHD FAEZ, AHMAD FAHMI; CHE DALIM, CHE SAMIHAH (Applied Information Technology And Computer Science, 2025)
The Bakery and Pastry Arts course at UTHM is designed to equip students with essential baking knowledge and hands-on skills through practical modules and kitchen-based training. However, traditional methods face challenges such as high resource consumption, time constraints, and limited practice opportunities. To overcome these issues, KitchenLab was developed as an innovative Virtual Reality (VR) application tailored for UTHM bakery students. Guided by SME Dr. Siti Hajar Binti Zakariah, the app follows the TRES-D methodology, which emphasizes iterative evaluation, design, development, and testing. KitchenLab simulates critical baking stages, including preparation, proofing, and baking, offering an immersive and efficient learning alternative. To assess usability, the System Usability Scale (SUS) was administered to 20 UTHM bakery students. The application achieved an average SUS score of 73.75, indicating above-average usability and positive user acceptance among its target users.